Affirmative action and team performance - Felix Kölle (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We experimentally investigate spillover effects of affirmative action policies in tournaments on subsequent team performance and the willingness to work in teams. In three different team environments, we find that such policies in form of gender quotas do not harm performance and cooperation within teams, and do not weaken people's willingness to work in teams. Our results, thus, provide further evidence that gender quotas can have the desired effect of promoting women without harming efficiency.
Keywords: C91; C92; D03; 330; affirmative action; teams; gender; performance; cooperation; selection; experiment